The Fantastic in the literature of the journey - Al - Rakeeb, Ashwaq Fahd (Arab Journal for Sciences and Research Publishing, 2019)
The research revolves around the concept of the Fantastic in the literature of the journey, where his image is clearly manifested in this literary art, and varied themes and forms.The field of research has been defined by two journeys representing the old and the modern: Ibn Battuta's journey, called "masterpiece of the nobles in the strangeness of the monuments and the wonders of travel"Anis Mansour's journey "Around the World in 200 Days"Research began with the concept of the journey language and terminology, and importance, and highlighted functions.Then the miraculous concept of a number of Arab and Western critics, and the most prominent manifestations in the texts of flights. With practical examples of the most miraculous elements: the miraculous event, the miraculous personality, and the miraculous place.The research ends with the most important findings, a list of sources and references.
Keywords: The concept of the fantastic; travel literature; literary criticism; Ibn Battuta; Anis Mansour